2021
DOI: 10.3390/agronomy11091745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recycled Waste Compost on Soil Food Webs, Nutrient Cycling and Tree Growth in a Young Almond Orchard

Abstract: Composting is an effective strategy to process agricultural and urban waste into forms that may be beneficial to crops. The objectives of this orchard field study were to characterize how a dairy manure compost and a food waste compost influenced: (1) soil nitrogen and carbon pools, (2) bacterial and nematode soil food webs and (3) tree growth and leaf N. The effects of composts were compared with fertilized and unfertilized control plots over two years in a newly planted almond orchard. Both dairy manure comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Additional composting is an effective strategy for converting agricultural and urban waste into forms that benefit crops. A study investigating the impact of using recycled compost on soil food webs, nutrient cycling, and tree growth in a young almond orchard showed that both dairy manure compost and food waste compost resulted in increased pools, soil, and ammonium levels [ 52 ]. Both composts had a noticeable impact on bacterial communities following application, particularly on groups capable of breaking down carbon [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional composting is an effective strategy for converting agricultural and urban waste into forms that benefit crops. A study investigating the impact of using recycled compost on soil food webs, nutrient cycling, and tree growth in a young almond orchard showed that both dairy manure compost and food waste compost resulted in increased pools, soil, and ammonium levels [ 52 ]. Both composts had a noticeable impact on bacterial communities following application, particularly on groups capable of breaking down carbon [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the impact of using recycled compost on soil food webs, nutrient cycling, and tree growth in a young almond orchard showed that both dairy manure compost and food waste compost resulted in increased pools, soil, and ammonium levels [ 52 ]. Both composts had a noticeable impact on bacterial communities following application, particularly on groups capable of breaking down carbon [ 52 ]. They resulted in increased nematodes that feed on bacteria at different intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of compost and compost-tea (CT) applications on soil fertility, plant growth, and the environment were evaluated in two research articles [11,12]. Dairy manure compost and food waste compost showed different effects on soil microbial community composition, but in both cases, the results suggested that recycled waste composts contribute to biologically based nitrogen cycling and can increase tree growth, especially within the first year after application [11].…”
mentioning
confidence: 99%
“…The effects of compost and compost-tea (CT) applications on soil fertility, plant growth, and the environment were evaluated in two research articles [11,12]. Dairy manure compost and food waste compost showed different effects on soil microbial community composition, but in both cases, the results suggested that recycled waste composts contribute to biologically based nitrogen cycling and can increase tree growth, especially within the first year after application [11]. CT application induced plant growth and defense in pepper plants against Phytophthora capsici and Rhizoctonia solani because of its relevant soluble nutrient content and microbiota richness, which provided a novel point for plant nutrition and protection in horticultural crops [12].…”
mentioning
confidence: 99%